The Euro Plus Pact: Competitiveness and external capital flows in the EU countries - Hubert Gabrisch; Karsten Staehr (Institut für Ost- und Südosteuropaforschung (IOS), 2012)
The Euro Plus Pact was approved by 23 EU countries in March 2011. The Pact stipulates a range of quantitative targets meant to strengthen competitiveness and convergence with the ultimate aim of preventing unsustainable financial imbalances from accumulating. This paper uses Granger causality tests and VAR models to assess the direction of causality between changes in the relative unit labour cost and the current account balance. The sample consists of the 27 EU countries for the period 1995-2011. The main finding is that changes in the current account balance affects changes in relative unit labour costs, while there is no discernable effect in the opposite direction. This suggests that the divergence in the unit labour cost between the core countries in Northern Europe and the countries in Southern and Central and Eastern Europe prior to the global financial crisis was partly the result of capital flows from the European core to the periphery. The results call into question the ability of the Euro Plus Pact to avert financial imbalances related to increasing current account deficits in future.
urn:nbn:de:101:1-2012112710472
Keywords: E61; F36; F41; 330; European integration; policy coordination; unit labour costs; current account imbalances; economic crisis